Galileo’s Discourse on the Tides - Sierotowicz, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2014)
The introduction to the first polish translation of Galileo’s letter on tides written in the begining of the year 1616 to cardinal Alessandro Orsini. The text of translation is organized in a new way, and integrated with the index of matters.